Effects of Breed and Sex on Performance and Blood Characteristics of Three Commercial Broiler Strains - Olawale Mojeed Akanbi; Kabiru Oladapo Hammed; Hiqmat Busayo Lawal (Acta Scientiarum. Animal Sciences, 2025)
This study was conducted to compare three strains (Arbor Acre, Cobb and Marshal) of broiler chickens using growth traits and biochemical profile with the view of identifying the best strain in the broilers. The experiment was conducted to investigate the performance and blood characteristics of three commercial broiler strains. 288 day-old of Arbor acre, Cobb and Marshall strains were used comprised of 96 birds per strains on a 12 replicates with 8 birds in a Completely Randomized Design (CRD). The birds were sexed and tagged using a wing tag. All data generated were subjected to 2 by 3 factorial in completely randomized design (CRD). Least square means of body weights indicated that strains had significant (p < 0.05) effect on the birds with Cobb having the highest weights compared to Arbore acre and Marshall. Body linear measurement also showed significant (p < 0.05) effect on all parameters on both sex and strains. Female birds showed significantly (p < 0.05) different than the male on mean cell volume, mean corpuscular haemoglobin only while the strain effect was significant on all haematological parameters measured. Furthermore, serum biochemical indices revealed that there was significant (p < 0.05) influence on strain and sex was not significantly (p > 0.05) influenced. It was, therefore, concluded from the study that Cobb performed better than Arbor acre and Marshall strains at 6 weeks and could be a better strain to attain maturity at a shortest possible period.